Sorbicillinoid-Based Metabolites from a Sponge-Derived Fungus Trichoderma saturnisporum - Junjun Meng; Wei Cheng; Hajar Heydari; Bin Wang; Kui Zhu; Belma Konuklugil; Wenhan Lin (Marine Drugs, 2018)
Antibacterial activity assessment and high performance liquid chromatography associated with nuclear magnetic resonance (HPLC/NMR) data revealed that the EtOAc extract of the fermented endophytic fungus Trichoderma saturnisporum DI-IA, obtained from the marine sponge Dictyonella incisa, contained conjugated olefinic metabolites with antibacterial activity. Chemical examination of the fungal strain resulted in the isolation of eight new sorbicillinoid-based compounds, namely saturnispols A–H (1–8). Their structures were determined on the basis of extensive spectroscopic analysis, including the experimental and calculated electronic circular dichroism (ECD) data for the configurational assignments. Saturnispol F exerted significant inhibition against a panel of bacteria strains including vancomycin-resistant enterococci (VRE) with a minimum inhibitory concentrations (MIC) ranging from 1.63 to 12.9 μg/mL, while saturnispol H showed selective effects against VRE and B. subtilis.